Free hand insertion of pedicle screws in Dorsal / Lumbar / Sacral spine – Our experience - Bijukachhe, B; Shrestha, BK; Pandey, JR; Banskota, AK (Nepal Orthopaedic Association Journal, 2013)
Background: Fluoroscopic guidance to put pedicle screws helps to confirm the accuracy of the screw in place; however, it is always not mandatory Methods: In 79 patients, 531 pedicle screws were inserted during a period between July 2006 and November 2009. There were 218 pedicle screws in trauma, 138 in TB spine, 107 in Scoliosis, 26 in Scheuermann’s kyphosis, 18 in Spondylolysis / spondylolisthesis and 24 in tumors. In lumbar / sacral region total of 140 screws and in Dorsal region 391 screws were introduced. All screws were inserted free hand without fluoroscopic guidance. Accuracy of the placement was checked per operatively with pedicle probe by sounding technique. Before wound closure and whenever in doubt position of screws was checked under fluoroscope. Post operatively patients were subjected for CT scan to confirm the position of the screws. Seventeen patients with 107 screws were excluded from the study since they were not subjected for post-operative CT scan. The study consisted of 424 pedicle screws in 62 patients. Results: Out of 424 pedicle screws four screws (0.9%) were misplaced. Three patients complained of dysesthesia. Eleven screws (2.5%) were broken at last follow up of 12.6 months. The average surgical time for insertion of the screw without image intensifier is four minutes whereas with image intensifier was 7.5 minutes. Conclusion: Free hand insertion of pedicle screws is safe and time saving. DOI: http://dx.doi.org/10.3126/noaj.v2i1.8138 Nepal Orthopaedic Association Journal Vol.2(1) 2011: 35-42